Marketing a strategie rozwoju polskich gmin - Nowacki, Robert (Marketing and Strategy for Development of Polish Municipalities, 2008)
Management of a territorial unit requires creating its competitiveness in acquisition of investment capital and attraction of tourists and new dwellers. This is served by a strategy for local development, which integrates therein a number of activities aimed at an increase of attractiveness of the municipality against the background of other ones. The surveys carried out among the municipality offices (creators of the strategy for local development) and local enterprises (beneficiaries of the gains resulting from usage of these strategies) show that the tools of territorial marketing are used more and more often for this purpose. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 329-338